The performance of a multilevel multifunctional solar inverter under various control methods - Darshni M. Shukla; Naimish Zaveri; Tole Sutikno (Bulletin of Electrical Engineering and Informatics, 2023)
Photovoltaic (PV) inverters are now supposed to provide additional supporting services with more reliability and efficiency. This paper presents three different control methods for generating reference current in a multifunctional, multilevel grid-tied PV inverter for harmonic, reactive, and unbalance compensation. These methods are the synchronous reference frame (SRF) theory (d-q), the instantaneous reactive power (IRP) theory (p-q), and the conservative power theory (CPT). As a result, the primary goal is to propose a low-cost multifunctional solar invert for distributed generation, with an appropriate prototype developed in the laboratory for experimental validation of various modes of operation. Demonstrated results show that the presented inverter is capable of providing various ancillary services with all three types of control.